Profiling of Passengers by E-Hailing Services in Malaysia - Salim, Salman; Salman, Mohamad Amirul Haziq; Salman, Mastura Najiha (Multidisciplinary Applied Research and Innovation, 2021)
Shared mobility is one of the unavoidable impacts of the Industrial Revolution 4.0. This mode of travel is rapidly spreading among the local road users. However, there is lack of study on the actual perception of share mobility concept in Malaysia. This study will analyze the actual opinion and perception of Malaysia people particularly the users of shared mobility services also aims to investigate the factors that influence the passengers towards the use of e-hailing services. The independent variables of this research are relative advantage, ease of use, trialability, social influence and safety of using e-hailing application. A survey was conducted among e-hailing users in Malaysia. The survey consisted of two parts; the first part contained general questions about gender, age, ethnic, employment, state and preferred types of transportation between e-hailing and taxi. The second part was the major part of the questionnaire which consisted of relative advantage of e-hailing services, ease of using e-hailing services, trialability of e-hailing application, social influence and safety provided by e-hailing services. Therefore, the questionnaire was constructed according to those significant factors. The correlation analysis was used to identify the relationship between independent variables and dependent variable. From the results obtained, the linear regression showed that the relative advantage, ease of use, trialability, social influence and safety indicated a positive significant relationship with the factor that influences the passengers. Among the variables studied, the ease of use showed the most significant factor that influences the passengers to choose e-hailing services in Malaysia with Cronbach’s Alpha of 0.874. In conclusion, this study shows some important information and provides benefits particularly to e-hailing services company to be more competitive in this industry by understanding the needs and concerns of passengers when they adopt the e-hailing services.